A Janus oil barrel with tapered microhole arrays for spontaneous high-flux spilled oil absorption and storage. Issue 41 (9th August 2017) - Zhang, Zhen; Zhang, Yinghui; Fan, Hua; Wang, Yulong; Zhou, Chen; Ren, Feifei; Wu, Sizhu; Li, Guoqiang; Hu, Yanlei; Li, Jiawen; Wu, Dong; Chu, Jiaru
Abstract : A novel Janus oil barrel with tapered microholes is fabricated for the first time for the remediation of oil spill accidents. Abstract : Porous oil/water separation materials show excellent prospects in the remediation of oil spill accidents. However, several drawbacks such as low flux, limited absorption and storage capacity restrict their practical applications. Hence, a novel Janus oil barrel (superhydrophobic outside wall and superhydrophilic inside wall) constituted by tapered microhole arrayed aluminium foil is designed, which is demonstrated to be a promising device for the remediation of oil spill accidents. Furthermore, the investigation shows that the tapered microholes (taper angle 25–30°) can significantly enhance oil/water intrusion pressures (1–3 times higher than cylindrical holes) and unidirectional transferability which can eliminate the secondary leakage when salvaging full oil barrels without an additional procedure. It is indicated that the Janus oil barrel can spontaneously absorb spilled oil with a high flux (45 000 Lm −2 h −1 ), and synchronously store the absorbed oil. In addition, the barrel can absorb oil from surfactant-free oil-in-water emulsions appearing in oil spills and industrial processes. The distinct design combining excellent controllability, high precision and flexibility of the femtosecond laser micro/nanofabrication technology provides a general strategy in oil spill remediation.